Applications of HRM with A Reference of Learning and Development: Enhancing Organizational Performance through Learning and Development (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Learning and development is the field which is concerned with organizational activity aimed at bettering the performance of Individuals and groups in organizational setting. It is a combined role often called human resources development (HRD) meaning the development of “Human” resources to remain competitive in the marketplace.Learning focuses on doing activities today to develop employees for their current jobs and development is preparing employees for future roles and responsibilities. It carry out an analysis that the objective of learning and development is to creative learning organizations which ensure that employees through value addition can effectively perform their jobs, gains competitive advantage and seek self-growth this measurable performance resulting from good learning and development, shall enhance organization development. It is a process transferring information and knowledge to employers.